Application of the Book ”Durusu al Lughah al Arabiyah” on Arabic Learning/ استخدام كتاب "دروس اللغة العربية" في تعليم اللغة العربية - Jamilah, Mimi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
There are two studies in this discussion: How to learn in Arabic and use the book "Durusu Al Lughah Arabiyah in learning Arabic." Therefore, this research will discuss "The use of the book" Durusu al lughah al Arabiyah "in Arabic learning." The research objectives are as follows: 1) To determine learning in Arabic and 2) to determine the use of the book "Durusu Al-Lughah Al-Arabiyyah" in learning Arabic. To identify these problems in-depth and thoroughly, this study used a qualitative research method. The results of the study found that: In the book "Durusu Al-Lughah Al-Arabiyyah" there is about maharah istima ', qiro'ah, kalam, and kitabah, the book is also easy to learn by students, who learn Arabic using the book "Durusu Al-Lughah Al-Arabiyyah”.